2020
DOI: 10.1007/s42853-020-00074-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Simulation Study of Dynamic Characteristics of Hot Pepper Harvester

Abstract: Purpose Determining the safety conditions of a hot pepper harvester to mechanize harvesting. Methods The dynamic characteristics of a hot pepper harvester were analyzed with the dynamic simulation program RecurDyn. Results The pepper harvester can climb a maximal slope of 25° under full loading conditions; the maximal allowable height of an obstacle over which the harvester can drive is 450 mm; the minimal rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The results showed that the natural frequency decreased with increasing fruit maturity. In addition, the as yet partially studied mechanized harvesting simulation for crops was also applied to crops such as chickpea (Golpira, 2013), banana (Guo et al, 2021), and pepper (Kang et al, 2020). Although the harvesting methods are slightly different in every case, simulation analysis has become essential in crop harvesting research.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the natural frequency decreased with increasing fruit maturity. In addition, the as yet partially studied mechanized harvesting simulation for crops was also applied to crops such as chickpea (Golpira, 2013), banana (Guo et al, 2021), and pepper (Kang et al, 2020). Although the harvesting methods are slightly different in every case, simulation analysis has become essential in crop harvesting research.…”
Section: Introductionmentioning
confidence: 99%